Pengembangan Media Pembelajaran PAI berbasis Powerpoint di SDN 2 Depok - Tiara Indriarti; Muh. Alif Kurniawan; Vita Yuliana; Riska Anisa Indriyani; Eqviesta Runtun Pamungkas (STIKes Ibnu Sina Ajibarang, 2023)
The development of instructional media encompasses all tools that can be developed to assist teachers in delivering messages to students, thereby creating a clearer, engaging, efficient, and effective learning process. The aim of this research is to understand the development of instructional media in Islamic Education (Pendidikan Agama Islam or PAI) focusing on PowerPoint. The research method employed is qualitative with a field study conducted at SDN 2 Depok, Panjatan Kulonprogo. The results of this study indicate that the development of learning media based on PowerPoint for the subject of Islamic Education has a positive and responsive impact on first-grade students at SDN 2 Depok. The material, which was previously somewhat abstract due to a reliance on textual explanations, becomes more concrete and easily comprehensible when presented using videos and images, directly aiding students' understanding.